Analisa Implementasi IoT Pada Alat Microplate Incubator Pengembangan Pada Alat Elektromedik - Ulina, Sri; Sipayung, Apriska Dewi; Primasyukra, Mhd Aldi; Harefa, Juni Petranita; Hutagaol, Pio Lundu (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
The microplate incubator is an essential electromedical device designed to maintain optimal conditions during the incubation of blood samples, particularly in clinical laboratory examinations. This study aims to analyze the implementation of the Internet of Things (IoT) in a microplate incubator integrated with the Blynk application to improve the effectiveness of temperature and time control throughout the incubation process. The research method involved designing a microcontroller-based system equipped with a temperature sensor and wireless communication module, enabling real-time monitoring and remote control via Blynk. Performance testing was conducted by comparing temperature stability and timing accuracy between the IoT-based incubator prototype and a conventional incubator. The results demonstrated that the IoT system successfully maintained incubation temperature within a stable range, with deviations of less than ±0. 5°C, and provided remote accessibility for users. Therefore, the integration of IoT through Blynk in a microplate incubator enhances accuracy, efficiency, and user convenience in electromedical device development, with potential to support the digitalization of clinical laboratory services in the future.